2011
DOI: 10.1039/c0cs00211a
|View full text |Cite
|
Sign up to set email alerts
|

Photodeposition of metal sulfide quantum dots on titanium(iv) dioxide and the applications to solar energy conversion

Abstract: Heteronanojunction systems consisting of narrow gap semiconductors represented by metal sulfides and TiO(2) are highly expected as visible-light-active photocatalysts and the key materials for various photoelectrochemical devices. The common central issue is increasing efficiency of the light-induced interfacial electron transfer from the metal sulfide quantum dots (QDs) to TiO(2). We have newly developed simple and versatile low-temperature photodeposition techniques for directly coupling metal sulfide QDs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
172
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 224 publications
(175 citation statements)
references
References 85 publications
2
172
0
1
Order By: Relevance
“…Although the use of semiconductors for photochemical water splitting dates back to a report by Fujishima and Honda in 1972 with TiO 2 and UV light, the challenge was to use SCs with absorption maxima that better matched the solar spectrum (66). There have been numerous reports describing efforts in this direction and several recent reviews offer a summary of systems used and results obtained (67)(68)(69)(70)(71)(72)(73)(74)(75). Semiconductor nanoparticles that exhibit size-constrained electronic properties represent a large and important class of possible light absorbers for the two half-reactions of water splitting.…”
Section: Significancementioning
confidence: 99%
“…Although the use of semiconductors for photochemical water splitting dates back to a report by Fujishima and Honda in 1972 with TiO 2 and UV light, the challenge was to use SCs with absorption maxima that better matched the solar spectrum (66). There have been numerous reports describing efforts in this direction and several recent reviews offer a summary of systems used and results obtained (67)(68)(69)(70)(71)(72)(73)(74)(75). Semiconductor nanoparticles that exhibit size-constrained electronic properties represent a large and important class of possible light absorbers for the two half-reactions of water splitting.…”
Section: Significancementioning
confidence: 99%
“…Also, PbSe is known to possess a much larger Bohr radius (46 nm) than PbS (20 nm) [16]. For this feature, the band edge levels or the band gap can be easily controlled by the quantum confinement, which is important for the efficient electron injection into TiO 2 to be achieved [9]. Further, recent studies have demonstrated that PbSe has a great potential for enhancing the efficiency of solar cells through the multiple exciton generation [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…This in-situ technique possesses the following unique characteristics. First, QDs are directly deposited on the TiO 2 surface without using linker molecules, which enables the efficient photoinduced interfacial electron transfer [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, semiconductor photocatalysis as a promising and eco-friendly technology has attracted extensive attention due to the energy shortages and environmental crisis problem [1][2][3][4][5][6] . Owing to the limitation of narrow light responsive range and fast recombination rate of photogenerated charge carriers [7][8][9][10][11] , photocatalytic technology doesn't achieve breakthrough in term of its practical application.…”
Section: Introductionmentioning
confidence: 99%